Implementation of Islamic Religious Education for Children with Special Needs: A Systematic Literature Review 2020-2025 - Muhamad Arif; Hazman Bin Hassan; Nur Halimatus Sakdiyah; Faridatul Umah (Urwatul Wutsqo: Jurnal Studi Kependidikan dan Keislaman, 2025)
Children with special needs have the same rights to receive good education, without exception in Islamic religious education learning as one of the learning that teaches how to become individuals with broad knowledge, both with fellow human beings and with God, based on this urgency, researchers want to study how to implement Islamic Religious Education (PAI) for Children with Special Needs (ABK)?, What are the challenges in implementing Islamic Religious Education for Children with Special Needs? What is the role of teachers in increasing the involvement of ABK in Islamic Religious Education learning? The method used is the systematic literature review method, in the last five years (2020-2025). The results of the literature findings will be analyzed using the PRISMA Flow diagram. The results show that the implementation of Islamic religious education for children with special needs has almost the same tendency as regular students, namely starting from planning, implementation in the classroom, and evaluation of learning outcomes. However, in practice, several challenges are still found, starting from; limited facilities and infrastructure, human resources/teachers, and training for teachers according to the needs of children. So the important role of teachers in increasing the involvement of children with special needs in learning is inevitable, some other roles of teachers are; providing assistance according to the limitations and needs of students, creating an inclusive learning space so that time and space management can provide a sense of justice, safety and comfort to students.